Dana Zakat, Kesejahteraan, Kelangsungan Usaha Dan Pengaruhnya Terhadap UKM Baznas Di Makassar - Hajering Hajering; Baharuddin Latief (Fakultas Ekonomi, Universitas Muslim Indonesia, 2019)
This study aims to analyze the influence of zakat funds, welfare and continuity of the BAZNAS Makassar City UKM. The population of this study is all SMEs that have received alms from BAZNAS in Makassar City. A sample of 74 SMEs were selected proportionally. Data were analyzed using multiple regression. The results of the study found that the zakat fund, welfare and business continuity had a positive effect on the SME City of Makassar. Partially, the business continuity variable is known as the dominant variable affecting BAZNAS UKM in Makassar City.